Longitudinal Change in the Relationship between Fundamental Motor Skills and Perceived Competence: Kindergarten to Grade 2 - Jeff R. Crane; John T. Foley; Patti-Jean Naylor; Viviene A. Temple (MDPI AG, 2017)
As children transition from early to middle childhood, the relationship between motor skill proficiency and perceptions of physical competence should strengthen as skills improve and inflated early childhood perceptions decrease. This study examined change in motor skills and perceptions of physical competence and the relationship between those variables from kindergarten to grade 2. Participants were 250 boys and girls (Mean age = 5 years 8 months in kindergarten). Motor skills were assessed using the Test of Gross Motor Development-2 and perceptions were assessed using a pictorial scale of perceived competence. Mixed-design analyses of variance revealed there was a significant increase in object-control skills and perceptions from kindergarten to grade 2, but no change in locomotor skills. In kindergarten, linear regression showed that locomotor skills and object-control skills explained 10% and 9% of the variance, respectively, in perceived competence for girls, and 7% and 11%, respectively, for boys. In grade 2, locomotor skills predicted 11% and object-control skills predicted 19% of the variance in perceptions of physical competence, but only among the boys. Furthermore, the relationship between motor skills and perceptions of physical competence strengthened for boys only from early to middle childhood. However, it seems that forces other than motor skill proficiency influenced girls' perceptions of their abilities in grade 2.